Fetishes and carvings of the Southwest - Branson, Oscar T. (Tucson, AZ Treasure Chest Pub., 1976)
Survey of carvings, usually very small, used for religious purposes by Indians in the American Southwest. Well illustrated. Minimal text
45529
Keywords: Southwest; Indian sculpture